2019
DOI: 10.1103/physrevmaterials.3.074406
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging revealing halved ferromagnetism in tensile-strained LaCoO3 thin films

Abstract: The enigma of the emergent ferromagnetic state in tensile-strained LaCoO3 thin films remains to be explored because of the lack of a well agreed explanation. The direct magnetic imaging technique using a low-temperature magnetic force microscope (MFM) is critical to reveal new aspects of the ferromagnetism by investigating the lateral magnetic phase distribution. Here we show the experimental demonstration of the rare halved occupation of the ferromagnetic state in tensilestrained LaCoO3 thin films on SrTiO3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
3
10
0
1
Order By: Relevance
“…In contrast, the impact of CD on the O-Co-O distances (∼ 0.1 Å) is at least one order of magnitude larger. Therefore, we suggest CD to be the reason for the experimentally observed distinct O-Co-O distances (3.86 Å at 90 K splitting up symmetrically into 3.76/3.98 Å at 295 K, 6 with some domains remaining NM, as it has been observed very recently for LCO films 25 ), instead of e g orbital order assisted by Jahn-Teller distortions. Shimizu et al reported a symmetry preservation across the spin transition, which is incompatible with Jahn-Teller distortions.…”
Section: Computational Detailssupporting
confidence: 71%
See 4 more Smart Citations
“…In contrast, the impact of CD on the O-Co-O distances (∼ 0.1 Å) is at least one order of magnitude larger. Therefore, we suggest CD to be the reason for the experimentally observed distinct O-Co-O distances (3.86 Å at 90 K splitting up symmetrically into 3.76/3.98 Å at 295 K, 6 with some domains remaining NM, as it has been observed very recently for LCO films 25 ), instead of e g orbital order assisted by Jahn-Teller distortions. Shimizu et al reported a symmetry preservation across the spin transition, which is incompatible with Jahn-Teller distortions.…”
Section: Computational Detailssupporting
confidence: 71%
“…[1][2][3] This holds in particular if the emerging FM domains are embedded in an insulating NM matrix. 25 Finally, we note that a similar electronic structure is obtained for all systems in the IS state throughout this work.…”
Section: Computational Detailssupporting
confidence: 68%
See 3 more Smart Citations